Establishment of multiplex PCR for detection of genes related to Quinolone resistance - Ngo Tat Trung; Dao Thanh Quyen; Phan Quoc Hoan; Thirumalaisamy P.P. Velavan; Le Huu Song (Vietnam Journal of Science, Technology and Engineering, 2018)
Background/aims: It has been shown that quinolone resistance arises due to mutations in the quinolone resistance-determining regions of the drug targets. This study aimed to optimise a multiplex PCR assay to track plasmid-mediated low-level quinolone resistance profiles.